Nanomaterials-Based Electrochemical Sensors: Properties, Applications, and Recent Advances - Ahmad, Awais; Ahmad, Awais; Verpoort, Francis; Khan, Anish (Elsevier Science, 2023)
As opposed to conventional electrochemical sensors, nanomaterials-based sensors are active and effective in their action with even a minute concentration of analyte. A number of research studies are bringing about an evolution in their development and advancement because of their unique and effective properties. Nanoscale electrochemical sensors have applications in almost every field of life including the detection of neurochemicals, heavy metals, energy components, body fluids, biological matrices, cancer relevant biomolecules, aromatic hydrocarbons, also in playing their role in food science because of their capability in providing quality control and safety. There is a need to develop these nanomaterials-based electrochemical sensors to be more widely available for accurate sensing of minute concentrations especially in the case of heavy metal detection, biofluids, and other biomaterials. This book outlines the major preparation, fabrication and manufacture of nanomaterials-based electrochemical sensors, as well as detailing their principle medical, environmental and industrial applications in an effort to meet this need.This book is a valuable reference source for materials scientists, engineers, electrochemists, environmental engineers and biomedical engineers who want to understand how nanomaterials-based electrochemical sensors are made, and how they are used. - Explains the techniques used for the fabrication and manufacture of nanomaterials-based electrochemical sensors - Discusses the major applications of nanomaterials-based electrochemical sensors in biomedicine and environmental science - Assesses the potential toxicity and other challenges associated with using nanomaterials-based electrochemical sensors